PENGARUH LIVE STREAMING TERHADAP FASHION PURCHASE INTENTION MELALUI JOY OF MISSING OUT SEBAGAI VARIABEL MEDIASI (STUDI PENGGUNA TIKTOKSHOP DIKABUPATEN KLATEN) - Hadi, Abdul; Aulia, Nova (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
Abstract Live streaming has become a popular marketing tool in the fashion industry, offering direct interaction that can influence purchasing decisions. However, JOMO, which is the satisfaction obtained from choosing not to follow trends or instant offers, also has the potential to influence consumer response to live streaming. The study aims to analyze the influence of live streaming in influencing fashion purchase intention through joy of missing out as a mediation variable. Sampling from the existing population of Tiktokshop users in Klaten district using purposive sampling techniques according to research needs and obtaining results of 130 respondents. The method of analysis uses path analysis for direct influence testing as well as test cylinders for mediation influence. The results show that live streaming has a positive influence on fashion purchasing intentions, and JOMO acts as a significant mediation variable. JOMO reduces the direct impact of the urgency created by live streaming, enabling consumers to make more purchasing decisions based on personal values and preferences.